Hydrodynamics of liquid flow in the model of theoretical stage with perfect displacement - Maleta, Vladimir; Taran, Vitaly; Maleta, Bogdan (My University, 2011)
Pursuant to Lewis' work [1], the use of combinations of various hydrodynamic models of liquid and vapor phases enhances the efficiency of component separation on the tray. The greatest effect is achieved upon perfect displacement by liquid and vapor and sing-direction movement of liquid on adjacent contact degrees. In such conditions the efficiency of Murphy's tray may significantly exceed the local efficiency and reach 200-300% Cannon [2] suggested the way of phase interaction, for which during the passage of vapor through the column the liquid doesn’t overflow from tray to tray and upon liquid overflow it doesn't mix on adjacent trays (cyclic process). In a series of works [3, 4] it was shown that upon comparison of stationary and cyclic process both by the time of mass transfer on the tray and by the phase interaction nature the cyclic process is similar to the stationary process upon sing-direction movement of liquid on adjacent contact levels and perfect displacement by liquid and vapor. A mathematical model of the hydrodynamic processes occurring in a periodic cycled plate column is developed and experimentally confirmed.
Keywords: теоретичний етап; час перебування; масоперенос; циклічні дистиляції; етап теоретичної моделі з ідеальною переміщення; theoretical stage model with perfect displacement; residence time; mass transfer; cyclic distillation; theoretical stage; кафедра машин і апаратів харчових та фармацевтичних виробництв